What are the blood lead levels of children living in Latin America and the Caribbean?. (April 2017) - Olympio, Kelly Polido Kaneshiro; Gonçalves, Cláudia Gaudência; Salles, Fernanda Junqueira; Ferreira, Ana Paula Sacone da Silva; Soares, Agnes Silva; Buzalaf, Marília Afonso Rabelo; Cardoso, Maria Regina Alves; Bechara, Etelvino José Henriques
Abstract: Introduction: Information on the prevalence of lead exposure is essential to formulate efficient public health policies. Developed countries have implemented successful public policies for the prevention and control of lead poisoning. In the United States, Canada, Japan and the European Union, for instance, periodically repeated prevalence studies show that blood lead levels (BLLs) in children have decreased overall. Although BLL of Latino children in the U.S. have also dropped in recent years, the geometric mean remains higher than that of white children. Little is known about lead exposure in children in Latin America and the Caribbean (LAC). In this review, we responded to two questions: What is currently known about lead sources and levels in children in LAC? Are there public policies to prevent children's exposure to lead in LAC? Method: We conducted a literature review covering the period from January 2000 to March 2014 in the PubMed and Lilacs databases to obtain English, Portuguese and Spanish language studies reporting the prevalence of BLLs in children aged 0–18 years living in LAC countries. No specific analytical method was selected, and given the scarcity of data, the study was highly inclusive. Results: Fifty-six papers were selected from 16 different LAC countries. The children's BLLs found in this review are high (≥ 10 μg/dL) compared to BLLs for the same age group in the U. S. However, most studies reported an association with some type of "lead hot spot", in which children can be exposed to lead levels similar to those of occupational settings. Only Peru and Mexico reported BLLs in children from population-based studies. Conclusions: Most BLLs prevalence studies carried out in LAC were in areas with known emission sources. The percentage of children at risk of lead poisoning in LAC is unknown, and probably underestimated. Thus, there is an urgent need to establish public health policies to quantify and prevent lead poisoning, specifically by prioritizing the identification and control of "hot spots". Highlights: The number of children at risk of lead poisoning in LAC is unknown; it is necessary to close this information gap. Priority should be given to the identification and control of "lead hot spots" in LAC. Strengthening and enforcing regulations to prevent lead exposure is urgent and should become a public health priority in LAC.